Hubungan kecemasan akademik dan efikasi diri dengan keberhasilan belajar siswa Sekolah Menengah Pertama - Mashudatul Laduniyyah; Suyanti Suyanti (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2022)
This study was conducted to determine the relationship between academic anxieety and self-efficacy on learning success of the students at Junior High School. This research uses correlational quantitative method. Participants of this study amounted 88 people who were selected based on convenience sampling technique. Data Analysis in this study used multiple regression with Jamovi for Windows. The results of this study indicate that academic anxiety has a negative and significant relationship to learning success dan learning success has a positive and significant relationship to self-efficacy.